Shai and Emmie star in to the rescure - Wallis Q.; Simon Schuster Books; Ohlin N.,Miller S. (New York: Simon and Shuster Books, 2018)
Third -grader-Shai is already busy with already busy with her mother away and the Student Orchesta's benefit concert coming up,but that does not stop her from helping a stray animal in her backyard.
Junior Fiction-Juvenile